Determinan Kejadian Stunting Pada Balita di Puskesmas Darul Imarah Kabupaten Aceh Besar - Mustika, Muhammad Fiqram; Ramadhaniah, Ramadhaniah; Amin, Fauzi Ali (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2023)
Stunting merupakan masalah yang masih dihadapi oleh dunia terutama pada negara miskin dan berkembang. Kabupaten Aceh Besar pada tahun 2020 sebesar 40% yang artinya prevalensi stunting di kabupaten Aceh Besar melebihi prevelensi Stunting di Indonesia. Tujuan penelitian ini untuk mengetahui faktor risiko penyebab terjadinya Stunting pada balita usia >6 - 59 Bulan Di Wilayah Kerja Puskesmas Darul Imarah Kecamatan Darul Imarah Kabupaten Aceh Besar Tahun 2022. Jenis penelian deskriptik analitik dengan desain penelitian case control. Populasi penelitian ini adalah balita. Sampel terdiri dari 100 balita stunting dan 100 balita tidak stunting. Pengumpulan data dilakukan bulan Juli s/d Agustus 2022. Data dianalisis dengan menggunakan uji ChiSquare. Hasil penelitian menunjukkan bahwa asupan lemak cukup 57.1%, tidak diberikan kolostrum 59.7%, tidak asi eksklusif 57.1%. Hasil uji chi-square diperoleh bahwa ada hubungan kolostrum (p=0,000 dan OR=4,448), ASI eksklusif (p=0,024 dan OR=1,831) dengan stunting pada balita di wilayah kerja Puskesmas DarulImarah tahun 2022.Kata Kunci: Stunting, Balita, Kolostrum, ASI, LemakStunting is a problem that is still being faced by the world, especially in poor and developing countries. In 2016 stunting cases in Aceh were 26.4%, and increased in 2017 to 35.7%. In Aceh Besar District in 2020 the prevalence of stunting is 40%, which means that the prevalence of stunting in Aceh Besar district exceeds the prevalence of stunting in Indonesia. The purpose of this study was to determine the risk factors for stunting inÂ toddlers aged > 6 - 59 months in the Darul Imarah Health Center Work Area, Darul Imarah District, Aceh Besar District in 2022. This type of analytic descriptive study was a case control research design. The population of this study were toddlers in the working area of the Darul Imarah Health Center. The sample consisted of a case sample of 100 respondents and a control sample of 100 respondents. Data collection was carried out from July to August 2022. Data were analyzed using the ChiSquare test. The results showed that toddlers who had sufficient fat intake were 57.1% (p=0.034 and OR=0.545), and toddlers who were not given colostrum were 59.7% while toddlers who do not receive exclusive breastfeeding by 57.1%. The results of the chi-square test showed that there was a relationship between colostrum and stunting (p=0.000 and OR=4.448). And exclusive breastfeeding (p=0.024 and OR=1.831). Based on the research conducted, it can be concluded that two variables have a relationship with stunting in toddlers in the working area of the Darul Imarah Health Center in 2022. It is hoped that the head of the Darul Imarah Health Center, Darul Imarah District, Aceh Besar District, will further improve relations with the community, one of which is by conducting routine health education to the community so that it will increase parents' knowledge of the causes of stunting in children.Keywords: Stunting, Toddlers, Colostrum, ASI, Fat